An efficient and green pretreatment to stimulate short-chain fatty acids production from waste activated sludge anaerobic fermentation using free nitrous acid. (February 2016) - Li, Xiaoming; Zhao, Jianwei; Wang, Dongbo; Yang, Qi; Xu, Qiuxiang; Deng, Yongchao; Yang, Weiqiang; Zeng, Guangming
Abstract: Short-chain fatty acid (SCFA) production from waste activated sludge (WAS) anaerobic fermentation is often limited by the slow hydrolysis rate and poor substrate availability, thus a long fermentation time is required. This paper reports a new pretreatment approach, i.e., using free nitrous acid (FNA) to pretreat sludge, for significantly enhanced SCFA production. Experimental results showed the highest SCFA production occurred at 1.8 mg FNA/L with time of day 6, which was 3.7-fold of the blank at fermentation time of day 12. Mechanism studies revealed that FNA pretreatment accelerated disruption of both extracellular polymeric substances and cell envelope. It was also found that FNA pretreatment benefited hydrolysis and acidification processes but inhibited the activities of methanogens, thereby promoting the yield of SCFA. In addition, the FNA pretreatment substantially stimulated the activities of key enzymes responsible for hydrolysis and acidification, which were consistent with the improvement of solubilization, hydrolysis and acidification of WAS anaerobic fermentation. Highlights: SCFA production was enhanced greatly by FNA pretreatment. FNA pretreatment could accelerate EPS and cell envelop disruption. FNA pretreatment favored solubilization, hydrolysis and acidification processes. FNA pretreatment inhibited methanogenesis process.